THE KEY FACTORS TO CREATE CUSTOMERS’ SATISFACTION AT ALFAMART MINIMARKET - Pratminingsih, Sri Astuti; Aliansyah, Andi Muh. Nur; Merlia, Ella (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this research was to examine the effect of product diversity, convenience and price on consumer satisfaction. The type of research used explanatory with a total sample of 150 respondents. Collecting data used a questionnaire with a Likert measurement scale. The data analysis method used validity and reliability test, correlation coefficient (R), regression test, coefficient of determination, significance of t test and F test with SPSS 20.0 application. The results showed a positive and significant influence between product diversity, convenience and price on consumer satisfaction. Variable product diversity has an effect of 18%, convenience of 20.1% and price has an influence of 41.7%. Companies need to pay attention to product diversity, convenience and price in developing marketing strategies in order to provide customer satisfaction.